THE FORM OF BALINESE PUSPANJALI DANCE THROUGH AN AESTHETIC APPROACH - Paramacitha, Ni Luh N Jeylita; Mariasa, I Nengah; Trisakti, Trisakti; Handayaningrum , Warih; Rahayu, Eko Wahyuni (PT. Hafasy Dwi Nawasena, 2025)
Dance is a form of expression that reflects human interaction with the environment and culture as a ritual or entertainment art. One of them, Puspanjali Balinese dance is categorized as an entertainment dance in the form of a new creation dance (Balih-balihan Dance). This research examines the aesthetics of the Puspanjali dance form which refers to the aesthetic theory of Satyam, Sivam, Sundaram. The methodology used is descriptive qualitative by conducting observations, interviews with Balinese dance experts and literature studies. The analysis shows that Puspanjali dance movements are performed repetitively consisting of Agem (Agem right and left), Tangkis (Ngegol, Ngegol Nyemak Saput, Angsel, Ngeseh, Jalan swinging hand ukel, Jalan swinging holding saput), Tangkep (Ngliyer, Seledet). This variety of motion refers to pure motion that only shows aesthetics without meaning. This research concludes that the aesthetics of Puspanjali dance form can be seen through the concept of satyam which categorizes Puspanjali dance presentation as Balih-Balihan dance and the concept of sundaram refers to the beauty of Puspanjali dance form. Through the aesthetic approach, this research increases the understanding of Puspanjali dance form.